Răspuns :
[tex]2^{-2}=(\frac{1}{2})^{2}=\frac{1^{2}}{2^{2}}=\frac{1}{4}=0,25[/tex]
[tex]3^{-3}=(\frac{1}{3})^{3}=\frac{1^{3}}{3^{3}}=\frac{1}{27}[/tex]
[tex]OBS!!![/tex]
[tex]\boxed{ n^{-m}=(\frac{1}{n})^{m}}[/tex]
[tex]\boxed{ (\frac{a}{b} )^{-c}=( \frac{b}{a} )^{c}=\frac{b^{c}}{a^{c}}}[/tex]
[tex]3^{-3}=(\frac{1}{3})^{3}=\frac{1^{3}}{3^{3}}=\frac{1}{27}[/tex]
[tex]OBS!!![/tex]
[tex]\boxed{ n^{-m}=(\frac{1}{n})^{m}}[/tex]
[tex]\boxed{ (\frac{a}{b} )^{-c}=( \frac{b}{a} )^{c}=\frac{b^{c}}{a^{c}}}[/tex]